2022
DOI: 10.1186/s13054-022-03964-8
|View full text |Cite
|
Sign up to set email alerts
|

Auxora vs. placebo for the treatment of patients with severe COVID-19 pneumonia: a randomized-controlled clinical trial

Abstract: Background Calcium release-activated calcium (CRAC) channel inhibitors block proinflammatory cytokine release, preserve endothelial integrity and may effectively treat patients with severe COVID-19 pneumonia. Methods CARDEA was a phase 2, randomized, double-blind, placebo-controlled trial evaluating the addition of Auxora, a CRAC channel inhibitor, to corticosteroids and standard of care in adults with severe COVID-19 pneumonia. Eligible patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Currently, some clinical trials have shown beneficial effects of some approved drugs on COVID-19, including IL6R antagonist 3 ACE inhibitor, 4 Peginterferon Lambda-1a, 5 fluvoxamine, 6 Calcium release-activated calcium (CRAC) channel inhibitors, 7 Janus kinase 1/2 inhibitor, 8 vitamin D. 9 In parallel, some experimental studies have identified a set of human proteins that interact with SARS-CoV-2, 10 and may provide drug targets for general coronavirus interventions. Some genetic and epidemiology studies suggested that drug response of COVID-19 differs among ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some clinical trials have shown beneficial effects of some approved drugs on COVID-19, including IL6R antagonist 3 ACE inhibitor, 4 Peginterferon Lambda-1a, 5 fluvoxamine, 6 Calcium release-activated calcium (CRAC) channel inhibitors, 7 Janus kinase 1/2 inhibitor, 8 vitamin D. 9 In parallel, some experimental studies have identified a set of human proteins that interact with SARS-CoV-2, 10 and may provide drug targets for general coronavirus interventions. Some genetic and epidemiology studies suggested that drug response of COVID-19 differs among ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…For these experiments we used the CRAC channel blocker CM4620 that, like BTP2, selectively inhibits CRAC channels (I CRAC ) (Zitt et al , 2004; Waldron et al , 2019). CM4620 has been used in a phase 2 clinical trial for COVID‐19 pneumonia (NCT04345614), in which it was reported to be safe and well‐tolerated with strong signals in both time to recovery and all‐cause mortality (Bruen et al , 2022) and in an ongoing phase 1/2 clinical trial for acute pancreatitis (NCT04195347). To confirm inhibition of CRAC channels by CM4620, we overexpressed STIM1 and ORAI1 in HEK293 cells to enhance I CRAC as reported (Peinelt et al , 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The intravenous formulation of CM4620, Auxora, has been administered in a Phase 2 trial of patients with severe COVID‐19 pneumonia (NCT04345614) where is was reported to be safe and well tolerated with strong signals in both time to recovery and all cause mortality (Bruen et al , 2022). Auxora was also reported to be safe and well tolerated in a Phase 2 trial (NCT03401190) of patients with acute pancreatitis and systemic inflammatory response syndrome (SIRS) (Bruen et al , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The third clinical trial study of Auxora is for the extended treatment of high-risk patients with critical COVID-19 pneumonia (CARDEA-Plus) ( https://www.clinicaltrials.gov/ct2/show/NCT05171920 ). Although this particular trial was withdrawn due to the declining COVID-19 cases, the data clearly suggest a promising effect of Auxora in treatment and management COVID-19 [53] .…”
Section: Sars-cov-2 Modulates Ca 2+ Signaling For ...mentioning
confidence: 97%
“…The inclusion of patients was done based on the baseline ratio of arterial oxygen partial pressure (PaO2 in mmHg) to fractional inspired oxygen (FiO2 expressed as a fraction), PaO2/FiO2 ≤ 200. The study reported that the recovery time was reduced to 7 days from 10 days for patients who received Auxora vs placebo [53] . The all-cause mortality rate with Auxora vs placebo on day 30 was 7.6% and 17.6% while on day 60 was 13.8% and 20.6% respectively [52] .…”
Section: Sars-cov-2 Modulates Ca 2+ Signaling For ...mentioning
confidence: 99%